The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1016/0014-2999(93)90866-g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of muscarinic receptorsmediating vasodilation in rat perfused kidney

Abstract: The muscarinic receptor mediating vasodilation of resistance vesse]s in the rat iso]ated, constant-pressure perfused kidney vasodilation disappeared after destruction of the endothelium with detergent. Highly significant correlations of agonist potencies for vasodilation were found between rat kidney and guinea-pig ileum submucosal arterioles as weH as agonist potencies at smooth muscle muscarinic M 3 receptors of the guinea-pig ileum. The rank order of antagonist potencies (4-diphenylacetoxy-Nmethylpiperidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 34 publications
5
44
3
Order By: Relevance
“…This is in agreement with previous data indicating direct M 3 receptormediated intestinal smooth muscle contraction (Eglen et al, 1994). The rank order of potency of telenzepine on muscarinic receptors is M 1 4M 3 4M 2 (Eltze et al, 1993;Waelbroeck, 1992), and for p-F-HHSiD it is M 3 4M 1 4M 2 (Lambrecht et al, 1989). The chosen dose of telenzepine in this study has earlier been shown to successfully inhibit M 1 receptordependent nerve-induced NO-formation from intestinal tissue, without a ecting the M 3 receptor-dependent contractile response (Iversen et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous data indicating direct M 3 receptormediated intestinal smooth muscle contraction (Eglen et al, 1994). The rank order of potency of telenzepine on muscarinic receptors is M 1 4M 3 4M 2 (Eltze et al, 1993;Waelbroeck, 1992), and for p-F-HHSiD it is M 3 4M 1 4M 2 (Lambrecht et al, 1989). The chosen dose of telenzepine in this study has earlier been shown to successfully inhibit M 1 receptordependent nerve-induced NO-formation from intestinal tissue, without a ecting the M 3 receptor-dependent contractile response (Iversen et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest a neuronal M 1 receptor-dependent NO release while endothelium derived NO release has been associated with muscarinic M 3 receptor activation as evident from studies in di erent vascular tissues (Ren et al, 1993;Eltze et al, 1993). Thus, a reasonable assumption may be that NO formation in di erent tissues is regulated by di erent receptor subtypes.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The mAChR antagonists used in the study reported here possess differing selectivity for the various mAChR subtypes, depending on their affinity patterns. Thus, the affinity pattern for pirenzepine 47 15,45,50 Affinity data for tropicamide are sparse, but this receptor antagonist appears to bind primarily to M 4 . 51,52 We are not aware of any receptor antagonists with high affinity for M 5 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…where C is the compound concentration, K is the EC 50 , and α describes the shape of the function (Hill coefficients with values > 1 describe curves with a flat low-dose region and high curvature, whereas values < 1 correspond to curves that increase rapidly). Significance of comparisons made on the basis of this model was determined by use of the likelihood ratio statistic, which yielded a χ 2 test.…”
Section: Data Analysis and Statistical Analysismentioning
confidence: 99%